ANALISIS KOMPETENSI MAHASISWA PADA PRAKTIK MANAJEMEN PENDIDIKAN ISLAM - Hadi, Rizal; Abidin, Munirul; Latif, Muhammad Sabri; Mu'in, Mohammad Lutfi Alil (Universitas Islam Negeri Alauddin Makassar, 2024)
The purpose of this research was to analyze the improvement of student competence in the internship program, in terms of four main aspects, namely personality, professional, social, and managerial competencies. The research method uses a qualitative approach with in-depth interview techniques with students of the Islamic Education Management Study Program at UIN Sunan Ampel Surabaya who carry out internships at several partner institutions. The results showed that the internship program contributed to improving student competence. In the personality aspect, students are able to understand job descriptions, carry out tasks well, show responsibility, and discipline at work. In the professional aspect, students show the ability to complete work according to the specified time, utilize work support facilities, manage activities, and determine management studies and their classification. In terms of social competence, students are able to adapt to the workplace, interact and cooperate with coworkers, and adapt to the work given. Finally, in the managerial aspect, students are able to plan, organize, implement, and control and evaluate the assigned tasks.